The Challenge of Election of Regional Heads with the E-Voting System in terms of Legal and Technological Aspects - Darmadi Djufri (International Journal of Artificial Intelligence Research, 2022)
In 2024, regional elections are scheduled to coincide. Transparency and accountability must be referenced in the election of regional leaders so that the results inspire confidence among all parties. E-voting is one of the debates that arise to ensure the effective and efficient implementation of the election. The e-Voting system can be deployed beginning with the collecting of voter information, the registration of prospective voters, the performance of voting, and the calculation of voting results. This system can be linked to the National Population System during the data gathering phase for prospective voters to recruit candidates who match the standards. Consequently, this study attempts to highlight the topic of research on the difficulties of regional head elections utilizing electronic voting technology. This study employs a qualitative, descriptive methodology. The results of the study indicate that the E-voting system in general elections is a system that is utilized more effectively and has complied with the election principle, namely Luber Jurdil, so that in the implementation of E-voting, a unique and explicit regulation can be formulated, both in the form of laws and Perppu. Because the election legislation itself has not been precisely regulated concerning electronic voting until this point, this study also illustrates the benefits and drawbacks of electronic voting